(untitled) (Journal of Cancer Research Updates, 2014)
We report a very rare case of coexistence of non-keratinizing nasopharyngeal carcinoma and follicular lymphoma in nasopharynx. A 52-year-old woman was admitted in our hospital because of painless enlarged bilateral cervical mass. Nasopharyngoscopy revealed a nasopharyngeal mass, and biopsy showed follicular lymphoma cells infiltrating non-keratinizing squamous carcinoma. The patient underwent combined treatment which targeted two tumors and was alive without any progression in one-year follow up.